BK virus associated haemorrhagic cystitis in related donor haematopoietic stem cell transplant recipients: a developing country experience - Noor, Misbah; Saifullah Khan Niazi; Hajra Farooq; Raheel Iftikhar; Eijaz Ghani; Parvez Ahmad (Journal of the Pakistan Medical Association, 2022)
A retrospective cross sectional study was conducted at the Virology Department, Armed Forces Institute of Pathology (AFIP) and Armed Forces Bone Marrow Transplant Centre (AFBMTC), Rawalpindi, from January 2016 to July 2018. Medical records of 193 patients were examined to determine the number of patients developing Haemorrhagic Cystitis associated with BK virus (BKV). BKV PCR testing was done on the patients’ urine samples. Cytomegalovirus reactivation was also assessed weekly from day 30 to day 100, by CMV quantitative PCR testing on blood samples. Out of 193 patients, 11 (5.6%) developed haemorrhagic cystitis and all these patients were positive for BKV on urine samples. The maximum number of positive cases, i.e. 5 (2.6%) was in the age group three months to 10 years. Primary disease in seven out of 11 cases was Beta-Thalassemia Major. Keywords: Haemorrhagic cystitis, Haematopoietic stem cell transplant, BK virus.